A legal analysis on the punishment for death by negligence under the penal code in Malaysia / Sharifa Nurliliyana Abd Karim, Afzan Hanim Md Zahary and Arnie Azreen Che Arifin - Abd Karim, Sharifa Nurliliyana; Md Zahary, Afzan Hanim; Che Arifin, Arnie Azreen (Faculty of Law, 2012)
Under Section 304A of Malaysia Penal Code it deals with the offence of causing death by negligence. Under this section, the amount of punishment provided is imprisonment of 2 years or fine or both. The problem with the available punishment is that, it is inadequate because the offence deals with the lives of another people, which will be endangered. Hence, it is not fair to simply provide for a punishment that is not proportionate with the offence. The purpose of carrying out this research is to look into further details regarding the existing punishment for the offence of causing death by negligence as in accordance with section 304A of the Penal Code of Malaysia, which was said to be inadequate. Comparisons are made between different countries, which involve United Kingdom (UK), India and Australia. This will help in assessing the appropriate amount of punishment that should be given to those offenders who commit the offence under this above-mentioned section. The conclusion obtained from this research is that the existing punishment for the offence of causing death by negligent under Section 304A of Penal Code should be amend in that a harsher punishment should be imposed towards the offenders.